Midgut volvulus without intestinal malrotation in a teenager: a case report - Yasmine Houas; Alma Baccouche; Nader Bennour Ghaddab; Sirine Fkaier; Riadh Jouini (Journal of Pediatric Surgery Case Reports)
Introduction: Midgut volvulus is a life-threatening surgical emergency typically associated with intestinal malrotation in neonates and infants. However, midgut volvulus without malrotation is rare and often underrecognized, particularly in older children, leading to delays in diagnosis and management. Case presentation: We present the case of a previously healthy 13-year-old male with a one-week history of intermittent, crampy abdominal pain and bilious vomiting. He was initially diagnosed with viral gastroenteritis and treated symptomatically, but symptoms persisted and worsened. On admission, he was afebrile but had a distended, tender abdomen without signs of peritonitis. Abdominal X-rays were inconclusive, showing nonspecific bowel gas patterns. An abdominal ultrasound showed no definitive abnormalities. Due to ongoing symptoms, a contrast-enhanced abdominal computed tomography (CT) scan was performed, revealing a classic “whirlpool sign” of the superior mesenteric vessels and proximal bowel dilation. The patient underwent emergency exploratory laparotomy. Intraoperatively, a 360° midgut volvulus was found, caused by congenital mesenteric adhesions. The bowel appeared viable. Detorsion and complete adhesiolysis were performed without the need for resection. The postoperative course was uneventful: oral feeding was reinitiated on postoperative day 2, and the patient was discharged on postoperative day 6. At three-month follow-up, he remained asymptomatic with no signs of recurrence. Conclusion: Midgut volvulus must be included in the differential diagnosis of teenagers who develop abdominal pain and/or bilious emesis.